Lessons from Best Practices for English Language Educational Reform in Thailand - Liengleam, Tanes; Sa-ngiamwibool, Amporn (Department of English Language Education, UIN Sunan Ampel Surabaya, 2017)
Lessons from other countries where digital technology is integrated into English classroom will shed lights to digital Thailand. This study, therefore, analyzed the best practices to extract and describe key success factors that could help increase national competitiveness. The conclusion of the study was drawn from an interpretive analysis and synthesis of the review of literature. Five purposefully selected best practices included Finland, Norway, the Netherlands and South Korea. This was a documentary study. The results revealed that key success that all these best practice countries share includes these ten issues: free, accessible, equalized education, ICT in English education, starting learning English in early age, professional development for teachers, stress on qualification of teachers, teacher compensations and welfares, small class size, assessment and testing reform and homework reform. Policy implications indicate that if the Thai government want to reach the educational efficiency of the best practice countries, it should take these issues into consideration. Future inquiry should include more countries to get a wider, more practical and more insightful holistic scope of the study.